Life Cycle Assessment (LCA) Case Study on Cement-bonded Particle Board Produced By Using Construction Demolition Wood Waste - AKIN, Ceren Serap; AR, İrfan and HACIOĞLU, Sibel (MAS Journal of Applied Sciences, 2023)
Construction and Demolition Waste (CDW) is currently seen as one of the most important concerns that national authorities, particularly in Turkey, which is in the process of urban transformation and located in an earthquake zone. The search for alternative secondary raw materials for industries that use wood and its derivatives as raw materials is an important issue with the decrease on forest resources. CDW consists of bulky materials such as asphalt, bricks, wood and plastic. The main purpose of this study is use of waste wood those obtained by recycling the construction and demolition wood waste (CDWW) as cellulose source in production of cement-bonded particle board (CBPP). For this purpose, alkali treatment of CDWW was carried out by using alkaline solutions at four different concentrations of 2%, 3%, 5% and 8% NaOH by using the dipping method. A new cement-bonded particle board design was made using these alkali treated CDWW. The mechanical and physical performance tests of the produced particle boards were carried out and a recipe that yield the particle board having the best results was determined and a life cycle assessment study was conducted. As the recipes were produced by holding the cement/wood (c/w) ratio stable at 2:1, the best results were obtained from the boards produced by using CDWW that treated with 2% NaOH. The modulus of rupture (MOR), modulus of elasticity (MOE) and density tests were applied to the produced boards in accordance with TS EN 310 and TS EN 323 standard, respectively. The vaules obtained as a results of MOR, MOE and density test are 10.37 N mm-2, 6437.28 N mm-2 and 1255.12 kg m-3, respectively. The experimental outcomes showed acceptable mechanical and physical performance of the developed CBPP in compliance with the required standards. The feasibility of the study was evaluated by conducting LCA studies for the most effective recipe. The global warming potential (GWP) value of the recipe with the best result as a 677.11 kg CO2 equivalent was found. The results of this study can be considered as an effective roadmap for sustainability in all over the world and in appling secondy raw metarial CDW management.